124k views
3 votes
7(-8)-2y=-52





help....

7(-8)-2y=-52 help....-example-1

2 Answers

7 votes

Answer:

Explanation:

x = -8 so replace x with -8.

It should be 7(-8) - 2y = -52

Multiply 7 and -8 you get -56

You are left with -56 - 2y = -52

add -56 on both sides to get it on the other side

You will be left with -2y = 4

Divide by -2y on both sides

You'd get y = -2

User Israkir
by
5.8k points
5 votes

Answer: Y = -2

Explanation:

7(-8) -2y = -52

-56 - 2y = - 52

- 2y = 4

Y = -2

User Carolyn Conway
by
5.8k points